Mental health consequences of early life stress in children - the autonomic nervous system as a potential target for early detection and intervention? - Venn, Rachel; Sigrist, Christine; Rudzki, Stephan; D'Cunha, Nathan M.; Buchhorn, Reiner; Koenig, Julian; Northey, Joseph M.; Naumovski, Nenad; McKune, Andrew J. (Psychoneuroendocrinology, 2025)
Early life stress affects children worldwide, influencing behavioural, social, emotional, cognitive, and physical development. It is strongly associated with an increased risk of mental illness across the lifespan, with symptoms often emerging during childhood or adolescence. Parents experiencing acute and chronic stress may inadvertently contribute to adverse health outcomes in their children, as cumulative exposure to stress within the family unit can negatively impact both mental and physical well-being. Children exposed to parental stress and its associated emotional and physiological responses may be at a heightened risk for autonomic nervous system (ANS) developmental disruptions. Disruptions in the ANS regulation are linked to metabolic risk, cardiovascular disease, type 2 diabetes mellitus, and early mortality, as well as mental illness. Autonomic imbalance, characterised by sympathetic overactivity and/or parasympathetic (vagal) underactivity, has been proposed as a key mechanism connecting early life stress to increased vulnerability to mental health disorders later in life. However, the strength of this association may depend on moderating factors such as the type of early adversity, presence of psychopathology, and age. Heart rate variability (HRV), particularly the root mean square of successive differences (rMSSD) and high frequency HRV, provides a non-invasive, cost-effective and accessible method for assessing vagal activity and ANS function. The steep increase in vagal activity observed during infancy and puberty represents critical periods in ANS development, making these phases particularly susceptible to early life stress. This review suggests that HRV-based assessments of vagal activity could serve as an early marker of ANS dysregulation, helping to identify children at risk of mental health conditions. Moreover, childhood presents a crucial window for targeted lifestyle interventions, such as exercise, to enhance vagal activity, potentially mitigating the long-term consequences of early life stress.